Penguatan Promosi MATIQ Al-Uswah Banyuwangi Melalui Pelatihan Digital Marketing Berbasis AI Menggunakan Platform Media Sosial - Syidada, Shofiya; Prasetya, Noven Indra; Karyanto, Nonot Wisnu (Universitas Wijaya Kusuma Surabaya, 2025)
The era of digital transformation has drastically changed the promotional and marketing landscape. Educational institutions, including Madrasah Aliyah (MA), need to adapt to these changes to be able to compete with other schools. Digital marketing, especially using social media, is not only uploading photos or videos, but requires an understanding of algorithms, content strategies, and data analysis to achieve maximum results. In addition, current artificial intelligence (AI) capabilities can assist in this process, from faster content creation, writing interesting captions, to targeting more specific audiences. Therefore, the community service (PkM) activity aims to improve the competence of the media and Public Relations team of Madrasah Aliyah Tahfidzul Qur'an (MATIQ) Banyuwangi in designing and executing effective school branding strategies on digital platforms and shifting from mere promotion to building a strong and sustainable institutional image. The results achieved from this PkM activity include (1) Improving the competence of the school media team in viewing social media as a strategic tool for building a brand. (2) Mastery of technical skills, namely compiling a structured content plan, creating more persuasive promotions by utilizing AI such as chatGPT or gemini.